2000
DOI: 10.1200/jco.2000.18.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Trial of Gemcitabine Plus Cisplatin Versus Cisplatin Alone in Patients With Locally Advanced or Metastatic Non–Small-Cell Lung Cancer

Abstract: For the first-line treatment of NSCLC, the regimen of gemcitabine plus cisplatin is superior to cisplatin alone in terms of response rate, time to disease progression, and overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
290
3
10

Year Published

2000
2000
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 652 publications
(312 citation statements)
references
References 15 publications
9
290
3
10
Order By: Relevance
“…Good median and 1-year survival have been consistently observed (Abratt et al, 1997;Crino et al, 1997;Einhorn, 1997;Shepherd et al, 1997). Three randomized phase III studies demonstrated the superiority of GC over other chemotherapy regimens (Cardenal et al, 1999;Crino et al, 1999;Sandler et al, 2000). It is likely that GC as an induction treatment may further improve survival in LAD-NSCLC patients.…”
mentioning
confidence: 97%
“…Good median and 1-year survival have been consistently observed (Abratt et al, 1997;Crino et al, 1997;Einhorn, 1997;Shepherd et al, 1997). Three randomized phase III studies demonstrated the superiority of GC over other chemotherapy regimens (Cardenal et al, 1999;Crino et al, 1999;Sandler et al, 2000). It is likely that GC as an induction treatment may further improve survival in LAD-NSCLC patients.…”
mentioning
confidence: 97%
“…This combination has shown significant activity in a number of tumour types and has become a standard regime in advanced lung cancer (Rinaldi et al, 2000;Sandler et al, 2000). However, increased toxicities resulted from combining gemcitabine with CDDP or carboplatin have been reported (Rinaldi et al, 2000;Sandler et al, 2000;Thomas et al, 2002).…”
mentioning
confidence: 99%
“…Phase II studies showed response rates between 18 -26% and a mild toxicity profile (Anderson et al, 1994;Gatzemeier et al, 1996;Halme et al, 1997;Yokoyama et al, 1997;Perng et al, 1997;Takada et al, 1998;Zatloukal et al, 1998;Ten Bokkel Huinink et al, 1999). The combination of cisplatin and gemcitabine in NSCLC has been evaluated in phase III trials, reporting response rates of 22 -41% and median survival between 8.1 and 9.7 months (Cardenal et al, 1999;Crino et al, 1999;Comella et al, 2000;Sandler et al, 2000;Schiller et al, 2002).…”
mentioning
confidence: 99%